ASSOCIATION OF DYSLIPIDAEMIA AND COMORBIDITIES WITH RISK FACTORS AMONG DIABETIC PATIENTS: A RETROSPECTIVE OBSERVATIONAL ANALYSIS. - Mishra, Prabhakar Bhushan; Jaiswal, Rajendra Prasad; Bhushan, Bharat (Student’s Journal of Health Research Africa, 2024)
Background Diabetes mellitus (DM) is a disease marked by hyperglycemia brought on by an imbalance between the action or cooperation of insulin and its secretion. Aim To determine how risk variables are related to dyslipidemia and comorbidities in patients with type 2 diabetes mellitus (T2DM). Materials and Methods An enrolment of 65 T2DM patients was made using the electronic medical record. The link between the patients’ dyslipidemia and current comorbidities and the available laboratory, clinical, and demographic data was looked for. The SPSS-23 software was used for statistical analysis. Results Out of the 65 T2DM patients, 19 (29.22%) were male and 46 (70.76%) were female, with a mean age of 60.12±10.49 years, according to the electronic health record. 31 (47.38%) participants had diabetes mellitus for more than ten years, and 44 (68.30%) subjects had poor glycaemic control (HbA1c > 7%). 21 (31.68%) of the participants in this study had hypertension (HTN), 22 (34.45%) had ischemic heart disease (IHD), 9 (13.84%) were obese, 2 (2.45%) had a stroke, and 53(82.76%) had dyslipidemia. Out of the 54 patients with dyslipidemia, 41 (62.44%) were receiving treatment for hypolipidemia. Conclusion Findings showed that comorbidities were linked to aging and that HTN, IHD, and dyslipidemia were prevalent comorbidities. The present patterns in T2DM comorbidities and symptomatology were brought to light by this investigation. All of these extremely morbid consequences of this avoidable illness can be avoided with effective management and control by early screening and encouraging patients to lead healthy lifestyles. Recommendations To prevent the unintended consequences of cardiovascular disorders, routine blood glucose, and blood lipid monitoring for the early identification of dyslipidemia and placing patients under medical management is recommended.